Future Job Prospects in Singapore - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 2005)
What forces have shaped our nation’s employment and remuneration record so far? Where is Singapore’s unemployment rate headed? What should policy-makers do about it? These are the questions tackled in this paper.